2018
DOI: 10.11138/fneur/2018.33.1.045
|View full text |Cite
|
Sign up to set email alerts
|

A role for accelerometry in the differential diagnosis of tremor syndromes

Abstract: SummaryAccelerometry is a reliable tool for gauging the occurrence, amplitude and frequency of tremor. However, there is no consensus on criteria for accelerometric diagnosis of tremor syndromes. We enrolled 20 patients with essential tremor (ET), 20 with dystonic tremor (DT), and 20 with classic parkinsonian tremor (PD-T), all meeting accepted clinical criteria. All the patients underwent dopamine transporter imaging (by means of single-photon emission computed tomography) and triaxial accelerometric tremor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The TSI can capture the time-varying behavior of a single oscillator, whereas FWHM might better characterize the shifting between multiple oscillators as has been previously proposed (Shaikh et al, 2008;Brittain et al, 2015;di Biase et al, 2017). In DT, there could be a number of oscillators with irregularity in both amplitude and frequency (Deuschl et al, 2001), or a superimposed dystonic contraction might disrupt tremor rhythmicity, leading to increases both in FWHM and TSI (Bove et al, 2018). An alternative hypothesis for increased tremor instability in DT might be that the results depend on tremor amplitude since there were differences in tremor amplitude among groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSI can capture the time-varying behavior of a single oscillator, whereas FWHM might better characterize the shifting between multiple oscillators as has been previously proposed (Shaikh et al, 2008;Brittain et al, 2015;di Biase et al, 2017). In DT, there could be a number of oscillators with irregularity in both amplitude and frequency (Deuschl et al, 2001), or a superimposed dystonic contraction might disrupt tremor rhythmicity, leading to increases both in FWHM and TSI (Bove et al, 2018). An alternative hypothesis for increased tremor instability in DT might be that the results depend on tremor amplitude since there were differences in tremor amplitude among groups.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics of dystonic tremor are coarse, jerky, irregular, directional, and asymmetrical. Electrophysiological studies showed that tremors in both DT and TAWD groups were smaller in magnitude but exhibited higher irregularity in terms of amplitude and frequency compared with essential tremor (ET) (Jedynak et al, 1991;Shaikh et al, 2008;Bove et al, 2018). However, regular oscillations similar to ET have also been demonstrated in various types of DTS (Rudzi nska et al, 2013;Shaikh et al, 2015), indicating that there might be overlap in tremor characteristics between DTS and ET.…”
Section: Introductionmentioning
confidence: 99%
“…The 4-12 Hz bands represent the typical range for entrained motor unit activity producing upper-limb tremor in dystonic tremor and essential tremor (Elble, 1986;Elble et al, 1994;Deuschl and Elble, 2000;Shaikh et al, 2008;Neely et al, 2015) and the 0-3 Hz band can also be elevated in essential tremor (Neely et al, 2015). Standard deviation of peak frequency was selected because tremor frequency can be more irregular across time in dystonic tremor relative to essential tremor (Shaikh et al, 2008;Bove et al, 2018).…”
Section: Force Data Statistical Analysismentioning
confidence: 99%
“…The authors tested this index on different datasets, achieving an accuracy between 82% (on a validation cohort) and 90% (testing cohort) in discriminating ET from PD. Bove et al (42) used triaxial accelerometers worn on the proximal one-third of the metacarpals, and evaluated differences in frequency, amplitude, coherence, and peak dispersion of resting and action tremor between PD, ET, and dystonic tremor (DT) subjects. They combined these parameters into three sets of at most five discriminating criteria (one set for each disease), achieving, respectively, the following values of sensitivity and specificity: for DT, 85 and 87.5%; for ET, 95 and 90%; for PD, 100 and 93%.…”
Section: Devices For Differential Diagnosismentioning
confidence: 99%